2015
DOI: 10.1093/infdis/jiv515
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Cytomegalovirus Transmission From HIV-Infected Women Randomized to Formula-Feed or Breastfeed Their Infants

Abstract: Preventing CMV acquisition may be a priority for HIV-exposed infants, but there is a narrow window of opportunity for intervention. Approaches that reduce maternal cervical and breast milk CMV reactivation may help delay infant infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…This observation is consistent with reports from observational studies reporting lower rates of CMV transmission in cohorts following the introduction of HAART, 20 and our own observation of later CMV transmission in successive cohorts studied over secular time, who were exposed to increasingly efficacious PMTCT regimens. 9,11,29 Our study is also consistent with a study in Malawi that found no difference between breast milk CMV DNA levels at 4-6 weeks postpartum in HAART-treated women compared to women receiving single-dose NVP. 23 Our data suggest the risk of CMV transmission was modified through mechanisms distinct from reducing breast milk CMV levels, such as maternal antibodies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation is consistent with reports from observational studies reporting lower rates of CMV transmission in cohorts following the introduction of HAART, 20 and our own observation of later CMV transmission in successive cohorts studied over secular time, who were exposed to increasingly efficacious PMTCT regimens. 9,11,29 Our study is also consistent with a study in Malawi that found no difference between breast milk CMV DNA levels at 4-6 weeks postpartum in HAART-treated women compared to women receiving single-dose NVP. 23 Our data suggest the risk of CMV transmission was modified through mechanisms distinct from reducing breast milk CMV levels, such as maternal antibodies.…”
Section: Discussionsupporting
confidence: 90%
“…In Kenya most HIV-exposed children acquire CMV in the first year of life, regardless of HIV status, 9 with breast milk a major route of transmission. 11 CMV DNA is found in the breast milk of nearly all HIVinfected women, and breast milk CMV DNA level is associated with the risk of infant infection. 12 During pregnancy, CMV reactivation is also common in the cervix and is associated with the risk of intrapartum CMV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…CMV may therefore act as an important pathogen in patients with impaired immunity whether this results from iatrogenic or HIV induced immunosuppression. The incidence of congenital or perinatal CMV is also greatly increased in women with underlying HIV infection …”
Section: Discussionmentioning
confidence: 99%
“…Women living with HIV have a higher risk of transmitting CMV than women without HIV, due to longer duration of CMV excretion and higher breast milk, cervical, and salivary CMV viral loads 40,41 . In the only randomised controlled trial of breastfeeding versus formula feeding, conducted among mothers living with HIV in Nairobi during the pre--antiretroviral therapy (ART) era, a secondary analysis of CMV transmission was undertaken in 138 breastfed and 134 formula--fed infants 42 . Overall, breastfed infants acquired CMV earlier than formula--fed infants (median age, 4.26 vs 9.87 months; P<0.001) and had a higher 1--year probability of CMV infection (0.89 vs 0.69; P<0.001), although the proportion with symptomatic infection was not reported.…”
Section: CMVmentioning
confidence: 99%